The Influence of Service Speed and Respectful Attitude of the Front Office on Guest Satisfaction at Manhattan Hotel Jakarta - Suesilowati, Suesilowati; Yashinta, Devinda Ana; Hidayat, Arif (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to determine the effect of speed of service and respectful attitude of front office staff on guest satisfaction at the Manhattan Hotel, Jakarta. The background of this study stems from the strategic role of the hotel industry in providing excellent service to guests, where the front office is the frontline factor determining first impressions and customer satisfaction. The study used a quantitative method with a survey approach. Data were collected through a questionnaire distributed to 65 respondents who were guests at the Manhattan Hotel, Jakarta. Data analysis was conducted using validity and reliability tests, multiple linear regression, and hypothesis testing (t-test and F-test) using SPSS. The results showed that speed of service had a positive and significant effect on guest satisfaction, respectful attitude also had a positive and significant effect on guest satisfaction, and both variables simultaneously had a significant effect on guest satisfaction. These findings underscore the importance of improving front office service quality, particularly in terms of speed and respectful attitude, to enhance guest satisfaction and hotel competitiveness